The Response of Young Adult Smokers and Nonsmokers in the United Kingdom to Dissuasive Cigarettes: An Online Survey. Issue 2 (29th November 2017) - Moodie, Crawford; Gendall, Philip; Hoek, Janet; MacKintosh, Anne Marie; Best, Catherine; Murray, Susan
Abstract: Introduction: The cigarette stick is an important communications tool as well as the object of consumption. We explored young adults' responses to cigarettes designed to be dissuasive. Methods: Data come from a cross-sectional online survey, conducted in September 2015, with 16- to 24-year-old smokers and nonsmokers ( N = 997) in the United Kingdom. Participants were shown images of a standard cigarette (white cigarette paper with imitation cork filter), a standard cigarette displaying the warning "Smoking kills" on the cigarette paper, and an unattractively colored cigarette (green cigarette paper and filter). They were asked to rate each of the three cigarettes, shown individually, on eight perception items, and to rate the three cigarettes, shown together, on how likely they would be to try them. Ordering of the cigarettes and questions, with the exception of the question on trial, was randomized. Results: The eight perception items were combined to form a composite measure of cigarette perceptions. For smokers and nonsmokers, the two dissuasive cigarettes (cigarette with warning, green cigarette) were rated significantly less favorably than the standard cigarette, and less likely to encourage trial. For cigarette perceptions, no significant interaction was detected between cigarette style and smoking status or susceptibility to smoke among never smokers. A significant interaction was found for likelihood of trying the cigarettes, with dissuasive cigarettes having a greater impact with smokers than nonsmokers. Conclusions: This study suggests that dissuasive cigarettes may help to reduce the desirability of cigarettes. Implications: The cigarette stick is the object of tobacco consumption, which is seen every time a cigarette is smoked. It is also an increasingly important promotional tool for tobacco companies. In this study, young adults rated two dissuasive cigarettes (a green colored cigarette and a cigarette displaying a health warning) more negatively than a standard cigarette, and considered them less likely to encourage product trial. Our findings suggest that it may be possible to reduce the desirability of cigarette sticks by altering their design, for example, with the addition of a warning or use of an unattractive color.